2009
DOI: 10.1056/nejmoa0902066
|View full text |Cite
|
Sign up to set email alerts
|

Strict Blood-Pressure Control and Progression of Renal Failure in Children

Abstract: Intensified blood-pressure control, with target 24-hour blood-pressure levels in the low range of normal, confers a substantial benefit with respect to renal function among children with chronic kidney disease. Reappearance of proteinuria after initial successful pharmacologic blood-pressure control is common among children who are receiving long-term ACE inhibition. (ClinicalTrials.gov number, NCT00221845.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
239
2
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 812 publications
(259 citation statements)
references
References 26 publications
8
239
2
8
Order By: Relevance
“…A larger randomized study showed that both losartan and enalapril decreased proteinuria in 268 children with normal or high blood pressure [16]. The ESCAPE trial [17] found that 5-year intensified BP control in 385 children with CKD who received a fixed dose of an ACE inhibitor, delayed the time to 50 percent reduction in glomerular filtration rate (GFR) or progression to ESKD more effectively than conventional BP control. Proteinuria decreased by more than 50 percent during the firs six months, but, unexpectedly, gradually increased thereafter towards baseline values despite good BP control in both treatment groups.…”
Section: Introductionmentioning
confidence: 99%
“…A larger randomized study showed that both losartan and enalapril decreased proteinuria in 268 children with normal or high blood pressure [16]. The ESCAPE trial [17] found that 5-year intensified BP control in 385 children with CKD who received a fixed dose of an ACE inhibitor, delayed the time to 50 percent reduction in glomerular filtration rate (GFR) or progression to ESKD more effectively than conventional BP control. Proteinuria decreased by more than 50 percent during the firs six months, but, unexpectedly, gradually increased thereafter towards baseline values despite good BP control in both treatment groups.…”
Section: Introductionmentioning
confidence: 99%
“…They were thus not treated with RAS inhibitors. Hypertensive patients with hypodysplasia were reported to benefit from strict control of BP with angiotensin converting enzyme inhibitors [13]. Also, albuminuria and proteinuria are correlated with disease progression in children with CKD [14].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies found that aggressive blood pressure control delays the progression of chronic kidney disease (CKD). These include the ESCAPE study, which found that aggressive blood pressure control in children with CKD resulted in better GFR and reduced progression to ESRD [14]; also a study conducted on an elderly population in Denmark concluded that a reduced incidence of ESRD in this population was associated with an increase in the prescription rates for anti-hypertensive drugs, especially RAAS blockade with angiotensin converting enzyme (ACE) inhibitors and angiotensin receptor blockade (ARB). Other studies such as the MDRD study found limited benefit in aggressive versus normal blood pressure control [15,] while other studies found no benefit beyond that of normal blood pressure control [16,17].…”
Section: Hypertension and Polycystic Kidney Diseasementioning
confidence: 99%